Additive interaction of family medical history of cardiovascular diseases with hypertension and diabetes on the diagnosis of cardiovascular diseases among older adults in India - Ahmed, Waquar; Dixit, Priyanka; Halli, Shiva (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThe present study aimed to examine the additive interaction of family medical history of cardiovascular disease (CVD) and self-reported hypertension and diabetes on the diagnosis of CVD among older adults aged 45 years and above in India. A family medical history of CVD in individuals with hypertension and diabetes could identify a subpopulation with a higher risk of CVD.MethodsThe study used the data from the Longitudinal Ageing Study in India (LASI) Wave 1 (2017–2018). The total sample size for the study was 58,734 older adults aged 45 years and above. An additive model was applied to determine the additive interaction effect of the family medical history of CVD with hypertension and diabetes on the diagnosis of CVD by calculating three different measures of additive interaction: the relative excess risk due to interaction (RERI), attribution proportion due to interaction (AP), and synergy index (S).ResultsThe prevalence of CVD was higher among hypertensive individuals with a family medical history of CVD (18.6%) than individuals without the coexistence of family medical history of CVD and hypertension (4.7%), and hypertensive individuals without family medical history of CVD (11.3%). On the other hand, the prevalence of CVD was higher among individuals with diabetes and family history of CVD (20.5%) than individuals without the coexistence of family history of CVD and diabetes (5.0%). Individuals with parental and sibling medical history had two times higher odds of having chronic heart diseases and strokes, respectively than those without parental and sibling history. In the adjusted model, RERI, AP, and S for CVD were 2.30 (95% CI: 0.87–3.74), 35% (0.35; 95% CI: 0.20–0.51), and 1.71 (95% CI: 1.27–2.28) respectively, demonstrating significant positive interaction between family medical history and hypertension on the diagnosis of cardiovascular diseases.ConclusionsThe present study revealed that in the additive model, the interaction effects of family medical history and hypertension were significantly positive on cardiovascular diseases even after adjustment with potential confounding factors. Therefore, it is crucial to consider the presence of family medical history of CVD among individuals with hypertension and diabetes measured in research and clinical practice.